Predicting the Difficult Neonatal Airway in Fetuses With Micrognathia, Oropharyngeal or Neck Mass Lesions: Two‐Center Experience With Fetal MRI - Goergen, Stacy; Christie, James; Jackson, Tracy; Smet, Maria‐Elisabeth; Robertson, Simon; Malhotra, Atul; Kroushev, Annie; Lovell, Mark (Prenatal diagnosis, 2024)
ABSTRACT Objective Neonatal airway compromise requiring intubation, due to micrognathia or a mass lesion obstructing the fetal airway, remains difficult but important to predict prenatally. We aimed to validate MR predictors of difficult neonatal airway (DNA) in a multicentre retrospective cohort of fetuses with micrognathia and oropharyngeal/neck masses. Method The radiology databases of two large Australian maternal–fetal medicine centers were searched for subjects meeting inclusion criteria: Pregnancies of > 18 weeks' gestation evaluated with prenatal ultrasound and MRI between 2007 and 2022 where either fetal micrognathia or a fetal cervical, oral or oropharyngeal mass was identified on prenatal ultrasound and MRI, and details of delivery/postnatal course were available including: nature of delivery, need for the fetal airway to be secured at delivery, degree of difficulty in airway securement, survival > 24 h postnatally. Imaging predictors of a difficult neonatal airway (DNA) were assessed blinded to these neonatal outcomes. Results Twenty‐six fetuses met the inclusion criteria. Oropharyngeal and neck mass location with polyhydramnios was 100% sensitive and 82% specific for DNA. JI < 5th centile with polyhydramnios was 83% sensitive and 70% specific. JI < 5th centile with polyhydramnios was associated with DNA in 80% of cases delivered by ex utero intrapartum (EXIT) delivery and none with non‐EXIT delivery mode. Conclusion A cervical or oropharyngeal mass with polyhydramnios predicted a difficult neonatal airway. Polyhydramnios with jaw index < 5th centile was less sensitive and less specific for a difficult neonatal airway.